LEAN HEALTHCARE APPLICATION IN A SURGICAL PROCEDURES APPOINTMENT SCHEDULING CENTER IN A MATERNITY - Paim, Rafael; Costa, Amanda; Carvalho, Jonathan de; Lima, Inácio Araripe Costa (Brazilian Journal of Operations & Production Management, 2016)
The study aimed to apply Lean Healthcare concepts and tools in surgical scheduling process. The intention was to structure and implement an appointment-scheduling central that was able to manage more effectively the demand for elective obstetrical surgeries in a neonatal maternity. The study used action research as a scientific method in order to solve a problem encountered in scheduling procedures involving employees in a cooperative and participatory improvement initiative. The method used was based on literature review, benchmarking visits and studies to identify good practices, and on current working condition analysis and comparison of indicators before and after the intervention. The Lean and TOC theoretical frameworks was used to improve the process, creating value for the patients and professionals, conducting root-cause analysis, identifying wastes and constrains, and proposing and implementing solutions. Using action research in the study and applying the concepts and tools was possible to reach different results as the 70% reduction in cancellations, the increase in the number of procedures scheduled in the units, and increased 97% level of appointment scheduling service among other results.